Explore Westonci.ca, the top Q&A platform where your questions are answered by professionals and enthusiasts alike. Join our platform to connect with experts ready to provide detailed answers to your questions in various areas. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
To factorize the quadratic expression \(x^2 + 27x + 162\), we follow these steps:
1. Identify the quadratic expression: \(x^2 + 27x + 162\).
2. Find the roots of the quadratic equation: To find factors, we look for values of \(x\) that satisfy the equation \(x^2 + 27x + 162 = 0\).
We use the quadratic formula:
[tex]\[ x = \frac{{-b \pm \sqrt{{b^2 - 4ac}}}}{2a} \][/tex]
where \(a = 1\), \(b = 27\), and \(c = 162\).
3. Calculate the discriminant:
[tex]\[ b^2 - 4ac = 27^2 - 4(1)(162) = 729 - 648 = 81 \][/tex]
The discriminant is positive \(81\), implying two real roots.
4. Find the roots:
[tex]\[ x = \frac{{-27 \pm \sqrt{81}}}{2} = \frac{{-27 \pm 9}}{2} \][/tex]
[tex]\[ x = \frac{{-27 + 9}}{2} = \frac{{-18}}{2} = -9 \][/tex]
[tex]\[ x = \frac{{-27 - 9}}{2} = \frac{{-36}}{2} = -18 \][/tex]
Therefore, the roots are \(x = -9\) and \(x = -18\).
5. Factorize using the roots: If \(x = -9\) and \(x = -18\), we can write the factorized form as:
[tex]\[ (x + 9)(x + 18) \][/tex]
6. Expand the factorized form to confirm:
[tex]\[ (x + 9)(x + 18) = x^2 + 18x + 9x + 162 = x^2 + 27x + 162 \][/tex]
The factorization is indeed correct.
7. Extract individual terms from the factorized form: The terms are:
- From \((x + 9)\): \(x\) and \(9\).
- From \((x + 18)\): \(x\) and \(18\).
Thus, the complete individual terms involved in the factorization are \(9\), \(x\), \(18\), and \(x\).
Given the options, the correct answer is:
[tex]\[ \boxed{9, 9x, 18x} \][/tex]
1. Identify the quadratic expression: \(x^2 + 27x + 162\).
2. Find the roots of the quadratic equation: To find factors, we look for values of \(x\) that satisfy the equation \(x^2 + 27x + 162 = 0\).
We use the quadratic formula:
[tex]\[ x = \frac{{-b \pm \sqrt{{b^2 - 4ac}}}}{2a} \][/tex]
where \(a = 1\), \(b = 27\), and \(c = 162\).
3. Calculate the discriminant:
[tex]\[ b^2 - 4ac = 27^2 - 4(1)(162) = 729 - 648 = 81 \][/tex]
The discriminant is positive \(81\), implying two real roots.
4. Find the roots:
[tex]\[ x = \frac{{-27 \pm \sqrt{81}}}{2} = \frac{{-27 \pm 9}}{2} \][/tex]
[tex]\[ x = \frac{{-27 + 9}}{2} = \frac{{-18}}{2} = -9 \][/tex]
[tex]\[ x = \frac{{-27 - 9}}{2} = \frac{{-36}}{2} = -18 \][/tex]
Therefore, the roots are \(x = -9\) and \(x = -18\).
5. Factorize using the roots: If \(x = -9\) and \(x = -18\), we can write the factorized form as:
[tex]\[ (x + 9)(x + 18) \][/tex]
6. Expand the factorized form to confirm:
[tex]\[ (x + 9)(x + 18) = x^2 + 18x + 9x + 162 = x^2 + 27x + 162 \][/tex]
The factorization is indeed correct.
7. Extract individual terms from the factorized form: The terms are:
- From \((x + 9)\): \(x\) and \(9\).
- From \((x + 18)\): \(x\) and \(18\).
Thus, the complete individual terms involved in the factorization are \(9\), \(x\), \(18\), and \(x\).
Given the options, the correct answer is:
[tex]\[ \boxed{9, 9x, 18x} \][/tex]
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.